السجع الكهان والقضايا في القرآن: دراسة وصفية: As-Saja’ of the Soothsayers and Issues in the Quran: A Descriptive Studies - Mohd Nawi, Muhammad Zulazizi (SIBAWAYH Arabic Language and Education, 2021)
يهدف هذا البحث إلى الدراسة السجع الكهان والقضايا في القرآن. والسجع أحد أنواع المحسنات اللفظية المستخدمة في علم البلاغة في اللغة العربية. هذا البحث يقدم الفهم والتبيان إلى من لم يفهموا عن السجع الكهان والقضايا بشكل موضوعي. وأما هذا البحث يقدم المنهج والصفي، يعني الباحث يحتاج الرجوع إلى المصادر من الكتب البلاغة الذين يتعلق بالسجع الكهان والقضايا. ويدرس هذا البحث عن السجع وجماله في علم البلاغة. سيقوم الباحث بالتعرف معنى علم البديع والسجع من الأمثلة عنهما حتى توضيح صورة علم البديع والسجع مفهومهما. ثم، يتحدث الباحث عن سجع الكهان والتعرف كهان الجاهلية المشهورين، والكهان الأغراق بالتفصيل. وأخيرًا ، يُظهر هذا البحث أنّ السجع تتضمن فيها القضايا واختلاف أقاويل العلماء في المسائل الإستعمال السجع في القرآن الكريم.The research aims at studying As-Saja’ of the Soothsayers and issues in the Quran. As-Saja’ is one of the several forms of Rhymed Prose in Arabic Literature. This research gives an understanding and explanation for those who didn’t understand As-Saja’ of the Soothsayers and its issues in the Holy Quran based on views among Muslim scholars. And this research focuses on analysis research based on a descriptive method that means the researcher refers to secondary sources from books of Arabic Literature that relate with As-Saja’. These research studies are about As-Saja’ and its specialty in Arabic Literature Knowledge. The researcher started this research with the explain meaning of Ilm Badi’ and As-Saja’ and give the instances until understanding it. Then, the researcher also discussed the soothsayers or diviners from Jahiliyah's famous era in detail. Finally, this research shows that As-Saja’ contains with the issues includes the different sayings of scholars regarding the use of As-Saja’ in the Holy Quran.Keywords: As-Saja’, the soothsayers or diviners, the issues, the Holy Qur’an